2016
DOI: 10.1242/dev.133272
|View full text |Cite
|
Sign up to set email alerts
|

Real-time 3D visualization of cellular rearrangements during cardiac valve formation

Abstract: During cardiac valve development, the single-layered endocardial sheet at the atrioventricular canal (AVC) is remodeled into multilayered immature valve leaflets. Most of our knowledge about this process comes from examining fixed samples that do not allow a real-time appreciation of the intricacies of valve formation. Here, we exploit non-invasive in vivo imaging techniques to identify the dynamic cell behaviors that lead to the formation of the immature valve leaflets. We find that in zebrafish, the valve le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 51 publications
5
95
0
Order By: Relevance
“…This initial clustering is followed by the appearance of cellular extensions towards the extracellular matrix, or cardiac jelly, which is the elastic acellular layer separating myocardium and endocardium [10,11]. Subsequent tissue remodeling occurs to form multilayered endocardial cushions consisting of ventricular and AVC-derived EdCs within the cardiac jelly, which in turn overlays the atrial-derived EdCs exposed to the lumen [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial clustering is followed by the appearance of cellular extensions towards the extracellular matrix, or cardiac jelly, which is the elastic acellular layer separating myocardium and endocardium [10,11]. Subsequent tissue remodeling occurs to form multilayered endocardial cushions consisting of ventricular and AVC-derived EdCs within the cardiac jelly, which in turn overlays the atrial-derived EdCs exposed to the lumen [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish the hypothesis that heart valve development relies on EMT processes remains to be elucidated. Recent studies describing how migratory cell behaviors are involved in heart valve morphogenesis suggest that EdCs may undergo partial EMT and migrate into the cardiac jelly as a coordinated sheet of cells [12,13]. Given the clinical potential of stem cellbased valve repair, there is a growing interest in understanding the genetic programs and developmental pathways regulating valve formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Canonical WNT signaling has been shown to be required for heart valve development in zebrafish embryos (Hurlstone et al, 2003). More recent studies in the fish have demonstrated that canonical WNT signals arise specifically in subendocardial, abluminal cells, a finding analogous to the high level of canonical WNT signaling observed in the subendocardial mesenchymal cells of the remodeling cushion in the developing mouse heart (Figure 5F and (Gitler et al, 2003)), and that these WNT signals are dependent upon hemodynamic forces (Pestel et al, 2016). WNTs are particularly well-suited for a role in converting hemodynamic forces sensed by endothelial cells to instructions transmitted to subendothelial cells during this remodeling process because WNT signaling is stringently paracrine (Farin et al, 2016), enabling differences in hemodynamic shear to drive precisely graduated signals at single cell resolution.…”
Section: Discussionmentioning
confidence: 55%
“…Analysis of cushion gene expression revealed a nearly complete loss of Wnt9b and markedly reduced levels of the known canonical WNT target genes Axin2 and Lef1 , as well as the WNT inhibitory proteins Notum and Apcdd1 (Figure 5A-C and Figure S5). A complex and dynamic pattern of expression of WNT ligands has been reported in developing heart valves (Alfieri et al, 2010), and reporters have shown abundant canonical WNT activity in the remodeling cushion (Bosada et al, 2016; Gitler et al, 2003) as well as in abluminal cells adjacent to the endothelial cells lining the site of valve development in the zebrafish heart (Pestel et al, 2016), suggesting that WNT signaling may play an important role in this process. However, the precise role played by WNTs in the remodeling of cushions to mature valves and the mechanisms that regulate WNT expression in the remodeling cushion have not been defined.…”
Section: Resultsmentioning
confidence: 99%
“…At 40 hpf, endocardial cushions start to transform into primitive valve leaflets (Beis et al, 2005;Martin and Bartman, 2009). The presence of epithelial-to-mesenchymal transition for Zebrafish valvulogenesis has been debated but not yet confirmed (Pestel et al, 2016;Steed et al, 2016b). Endocardial cushions remodel into primitive valve leaflets to prevent retrograde flow completely at 76 hpf (Scherz et al, 2008).…”
Section: Zebrafish Heart Developmentmentioning
confidence: 99%